Development of high performance Medium Access Control (MAC) protocol for wireless ad-hoc network - Phang, Jian Kai. (2013)
While wireless communication has become a major part of our everyday lifestyle, wireless ad-hoc network have gained many interests in various applications due to its ease of deployment and maintenance. As Media Access Control (MAC) is responsible for the distribution of transmission medium, and a gain in performance in a lower layer like MAC layer improves the network performance significantly, development of a high performance MAC protocol is the focus in this project.